Analisis Perbedaan Aktivitas Fisik dengan Kualitias Tidur pada Siswa SMP Negri 20 dan SMP Swasta Muhammadiyah di Kecamatan Sawangan Tahun 2022 - Diningsih, Yulia; Lestari, Nur Eni (Journal of Nursing Education and Practice, 2024)
Introduction: The quality of sleep in adolescents is greatly influenced by the process of physical and mental development during puberty. Habitual factors such as physical activity are also often associated with sleep quality. Objectives: This study aims to investigate differences in physical activity and sleep quality among groups of adolescents who are considered to have varying exposure to physical activity about their status as students. Method: This research is a descriptive analysis research, so this research uses cross-sectional research. The population in this study was 240 students in grade 8 at SMP Negeri 20 for the 2022-2023 academic year, and at Muhammadiyah Private Middle School for the 2022-2023 academic year as many as 90 students. The sampling technique was purposive sampling, the sample obtained was 48 people. The instrument used was a questionnaire consisting of a sleep quality questionnaire and a physical activity questionnaire. Physical activity was measured using the Activity Questionnaire For Older Children (PAQ-C), while sleep quality was determined using The Pittsburgh Sleep Quality Index. Bivariate analysis using the Spearman Rank test. Result: The results of the study show that the majority of the physical activity in the two groups of subjects above had heavy physical activity. Namely, in State Middle Schools it was 31(64.6%) while in Private Middle Schools it was 29(60.4%). The quality of sleep in both groups of subjects was that the majority of subjects had poor sleep quality. In State Middle School students it was 26(54.2%) and in Private Middle Schools it was 35(72.9%) Meanwhile, the a difference in physical activity and sleep quality in State Middle Schools and Private Middle Schools. Namely, sleep activity was 0.047b, while physical activity was 0.533b. Conclusion: There are differences in sleep quality and physical activity between State Middle Schools and Private Middle Schools.